RATUS-V TO REDUCE ALBUS FLUORINE: ALTERNATIVE TO TRADITIONAL MEDICINE IN INDONESIA - naning puji suryantini; Asirotul Ma'rifah; Ariu Dewi Yanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Fluor albus is prone to occur in women of reproductive age. Ratus-V can be a non-pharmacological therapeutic choice for treating albus fluorine. They consider this treatment can prevent fluorine albus and maintain moisture in intimate areas so that the cleanliness and intimate health of the area is maintained. The purpose of this study was to identify the effect of Ratus-V on Fluor Albus. This research uses Pre-experimental. The research design used was the One-Group Pretest - Posttest Design, with a population of all women working in the cable assembly section at PT. SAI Ngoro Mojokerto sub-district was 180 respondents. The sample in this study amounted to 30 respondents. The sampling technique uses Purposive Sampling. Statistical test results value = 0,000 where value < less than 0.005 means that H0 is rejected and H1 is accepted. meaning the influence of Ratus-V on fluor albus in women who work in cable assembly at PT. SAI Ngoro Mojokerto Regency. As for the conclusion of this study, working women who have entered childbearing age who have fluor albus can use Ratus-V as a natural vaginal treatment as well as an alternative non-pharmacological drug in dealing with fluorine albus. Keywords: Ratus-V, Fluor Albus